2021
DOI: 10.1136/bmjopen-2021-049497
|View full text |Cite
|
Sign up to set email alerts
|

Maternal characteristics associated with gestational weight gain in France: a population-based, nationally representative study

Abstract: ObjectivesTo provide nationally representative estimates of gestational weight gain (GWG) and identify maternal characteristics associated with inadequate GWG in France.DesignA population-based study using data from the French National Perinatal Survey: 2010 and 2016.SettingAll maternity units in metropolitan, mainland France (n=535 in 2010; n=493 in 2016).ParticipantsSingleton live births with GWG data (N=24 850).Primary outcome measuresGWG was calculated as end of pregnancy minus pre-pregnancy weight (kg) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 57 publications
2
6
1
Order By: Relevance
“…In a study conducted in France, Amyx et al demonstrated that women with underweight pregestational BMI had a higher prevalence of inadequate GWG (OR 1.4 CI 1.2-1.5). Contrary to our results, the same authors found that patients with obese pregestational BMI tended to develop inadequate GWG (OR 1.5; CI 95% 1.4-1.7) [20]. They report that 15% of pregnant women are minors aged 25 or younger, but the proportion of adolescents is unknown.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study conducted in France, Amyx et al demonstrated that women with underweight pregestational BMI had a higher prevalence of inadequate GWG (OR 1.4 CI 1.2-1.5). Contrary to our results, the same authors found that patients with obese pregestational BMI tended to develop inadequate GWG (OR 1.5; CI 95% 1.4-1.7) [20]. They report that 15% of pregnant women are minors aged 25 or younger, but the proportion of adolescents is unknown.…”
Section: Discussioncontrasting
confidence: 99%
“…As noted previously, the French obstetric population has a healthier BMI profile than the USA obstetric population (Coulm et al, 2017;Deputy et al, 2018), which could reflect cultural differences which also promote lower GWG, though lower GWG was observed in our cohort regardless of BMI. The Notably, the application of IOM GWG guidelines for singletons in France did not produce such different results (26.8% insufficient GWG; 37.0% adequate GWG; 36.1% excessive GWG [Amyx et al, 2021]). However, the of the IOM singleton guidelines differed substantially in that it was based on GWG associated with adverse outcomes rather than percentiles of GWG and included research commissioned in multiple singleton cohorts…”
Section: Resultsmentioning
confidence: 82%
“…Notably, the application of IOM GWG guidelines for singletons in France did not produce such different results (26.8% insufficient GWG; 37.0% adequate GWG; 36.1% excessive GWG [Amyx et al, 2021 ]). However, the derivation of the IOM singleton guidelines differed substantially in that it was based on GWG associated with adverse outcomes rather than percentiles of GWG and included research commissioned in multiple singleton cohorts (2 USA, 1 Danish; dates ranging from 1988 to 2003) in addition to published research (Rasmussen & Yaktine, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of excessive GWG ranged from 36 to 73% for women with obesity [ 15 16 , 42 45 ], from 36 to 54% for women with gestational diabetes [ 17 , 45 , 46 ] and from 41 to 64% for women with obesity and pregestational diabetes [ 46 , 47 ]. The higher prevalence of excessive GWG (76%) reported here for the three obesity grades may be the result of the combination of diabetes mellitus and obesity that characterized our study population.…”
Section: Discussionmentioning
confidence: 99%